Poetry and loss : the work of Eugenio Montejo - Roberts, Nicholas, Dr (Colección Támesis. Monografías, 2009)
In a study which covers the entirety of Montejo's career as poet and essayist, this book examines how the work of this seminal Venezuelan writer explores and deals with the experiences of loss in the twentieth century. Focusing on the broad areas of tempo.